Barriers to transitioning towards smart circular economy: A systematic literature review - Lobo, Ana; Hofmann Trevisan, Adriana; Liu, Qinglan; Yang, Miying; Mascarenhas, Janaina (Springer, 2021)
This paper defines smart circular economy as an industrial system that uses digital technologies to implement circular strategies such as reduce, reuse, remanufacturing and recycling. The smart circular economy has been regarded as a promising approach to enhance sustainability. However, barriers exist in various stages of the transition towards smart circular economy. This paper employs a systematic literature review to identify the main barriers that prevent companies from this transition. We adopt a change management perspective to study this transition and propose that it follows a classical three-step process of organizational change: unfreeze, move, and refreeze. We identified 24 barriers in five categories: finance, management, infrastructure, network, and technology. Then, we placed the barriers into the three steps to further investigate how they affect each stage of the transition. Our analysis suggests that: (a) stakeholders play a central role in the process; (b) companies often have financial issues in the early steps of change; (c) technological challenges emerge in the advanced steps. The findings can help diagnose companies’ current status, identify solutions to tackle the barriers and predict future challenges.
Keywords: Smart Circular Economy; Sustainability; Digitalization; Change Management; Barriers